Effects of elastic-band resistance exercise on balance, mobility and gait function, flexibility and fall efficacy in elderly people - Kim, You Lim; Kwak, Cheol-Jin; Lee, Suk Min (Journal of Physical Therapy Science, 2016)
[Purpose] The purpose of this study was to analyze the effects of elastic-band resistance exercise on balance, gait function, flexibility and fall efficacy in the elderly people of rural community. [Subjects and Methods] It is selected by 45 outpatients. They have come into the clinic continually to treat of physical therapy at least 1–2 times for a week. A group treated with both general physical therapy and elastic-band resistance exercise (23 patients), and the other group treated with only general physical therapy (22 patients). Elastic-band resistance exercise is composed of 8 movements of lower extremity joints. It is performed for 30 minutes during 8 weeks by 3 times for a week. It is measured and recorded at the pre and post test that sit and reach test (SRT), functional reach test (FRT), timed up and go test (TUG) for every subjects by measurement equipments. And, subjects performed for the form of performance and question as its rated scale by Berg’s balance scale (BBS), dynamic gait index (DGI), activities-specific balance confidence scale (ABC). [Results] In the study, both the elastic-band exercise group and the general physical therapy group showed a significant improvement in balance, gait function, flexibility and fall efficacy. And the group with elastic-band resistance exercise showed more effectiveness than the contrast group in value of variation. [Conclusion] From this study, it was confirmed that elastic-band resistance exercise has influence on balance, gait function, flexibility and fall efficacy are working for agriculture of elderly people of rural community. Based on this result, elastic-band resistance exercise can be better instrument and easier to elderly people of rural community for the improvement in balance, gait function, flexibility and fall efficacy as it performing along with and reciprocal physical therapy.